Survivorship of patients with head and neck cancer receiving care in a tertiary health facility in Nigeria (2017)
Background: Head and neck cancer (HNC) is a major clinical and public health concern worldwide which impairs the vital functions of life. The treatment of metastatic HNCs is mainly palliative. This study examined the survival patterns and treatment outcomes in patients with HNCs in a tertiary hospital in Nigeria. Materials and methods: A review of the case files and treatment cards of patients with histological diagnosis of HNCs seen between January 2002 and December 2011 at the Radiotherapy Department, University College Hospital, Ibadan, was conducted. A total of 494 cases were identified, of which 481 had valid records. Analyses were done using Kaplan–Meier survival function and Cox proportional hazard regression techniques at 5% significance level. Results: The median age of patients was 42 years with a male-to-female ratio of 2:1. Most patients presented at stages 3 (50.7%) and 4 (36.8%). Nasopharyngeal carcinoma was the most common (42.6%) HNC, followed by paranasal sinus (17.7%) and laryngeal cancer (11.6%). The lung was the most common site of metastasis (25.5%). Patients who presented at stages 1 and 4 diseases had a median survival of 7.8 years and 1.9 years, respectively. Patients treated with a combination of chemotherapy and radiotherapy had a median survival of 8.0 years compared with those who had a single modality of treatment (~6.3 years). Conclusion: Patient survival was inversely proportional to the stage of the disease. To encourage the early presentation of HNC cases, health education of the population on routine medical check-ups and on the symptoms suggestive of HNC is recommended. Health care providers should be trained to refer suspected cases promptly to tertiary health facilities for management.